Impact of myo‐inositol trispyrophosphate (ITPP) on tumour oxygenation and response to irradiation in rodent tumour models. Issue 3 (21st December 2018) - Tran, Ly‐Binh‐An; Cao‐Pham, Thanh‐Trang; Jordan, Bénédicte F.; Deschoemaeker, Sofie; Heyerick, Arne; Gallez, Bernard
Abstract: Tumour hypoxia is a well‐established factor of resistance in radiation therapy (RT). Myo ‐inositol trispyrophosphate (ITPP) is an allosteric effector that reduces the oxygen‐binding affinity of haemoglobin and facilitates the release of oxygen by red blood cells. We investigated herein the oxygenation effect of ITPP in six tumour models and its radiosensitizing effect in two of these models. The evolution of tumour pO2 upon ITPP administration was monitored on six models using 1.2 GHz Electron Paramagnetic Resonance (EPR) oximetry. The effect of ITPP on tumour perfusion was assessed by Hoechst staining and the oxygen consumption rate (OCR) in vitro was measured using 9.5 GHz EPR. The therapeutic effect of ITPP with and without RT was evaluated on rhabdomyosarcoma and 9L‐glioma rat models. ITPP enhanced tumour oxygenation in six models. The administration of 2 g/kg ITPP once daily for 2 days led to a tumour reoxygenation for at least 4 days. ITPP reduced the OCR in six cell lines but had no effect on tumour perfusion when tested on 9L‐gliomas. ITPP plus RT did not improve the outcome in rhabdomyosarcomas. In 9L‐gliomas, some of tumours receiving the combined treatment were cured while other tumours did not benefit from the treatment. ITPP increased oxygenation in six tumour models. A decrease in OCR could contribute to the decrease in tumour hypoxia. The association of RT with ITPP was beneficial for a few 9L‐gliomas but was absent in the rhabdomyosarcomas.